Do You Imitate Immediately? The Location Choices for Foreign Direct Investment - Chung, H.; Liao, W.; Lin, Chad (Atlantis Press, 2015)
This study applies recency effect on interfirm imitation behavior to investigate whether recent location choices of peer firms regarding foreign direct investment (FDI) exert imitation pressure on another firm’s FDI location choices. This study examines the FDI data of listed companies in Taiwan. The results confirm the existence of recency effect. This study further indicates that the remote experience peer firms and a firm’s own experience have negative moderating effects on recency effect.